On scaling of proton- boron fusion power in a nanosecond vacuum discharge - Kurilenkov, Yu. K.; Andreev, S. N. (Frontiers in Physics, 2024)
In this paper, we present the results of further PiC simulations in the full electromagnetic code of the processes leading to the proton-boron reactions in a single device for plasma confinement, based on miniature nanosecond vacuum discharge (NVD) in a cylindrical geometry. In particular, we present and discuss in more detail the α particle output for the real electrodes geometry used in the first aneutronic protonboron fusion experiments with NVD. It follows from them that the total yield of α particles was accumulated in the initial experiments due to only single head-on converging of protons and boron ions accelerated in a very narrow potential well to the discharge axis. Next, basing on the numbers of proton-boron reactions obtained by simulations for different values of the virtual cathode radius in the anode space, the scaling of the proton -boron fusion power by the size of the virtual cathode is presented and discussed. The formation of more voluminous and a longer potential well, with well-defined oscillations of protons and boron ions in it, should provide an increase in the number of the proton-boron reactions. At the same time, an increase in the volume along the radius can lead to some saturation of the proton-boron reaction output, meanwhile the lengthening of the potential well with fusing ions along the discharge axis provides some increase of α particles yield.